2018
DOI: 10.3390/f9060367
|View full text |Cite
|
Sign up to set email alerts
|

Litterfall Production Prior to and during Hurricanes Irma and Maria in Four Puerto Rican Forests

Abstract: Hurricanes Irma and Maria struck Puerto Rico on the 6th and 20th of September 2017, respectively. These two powerful Cat 5 hurricanes severely defoliated forest canopy and deposited massive amounts of litterfall in the forests across the island. We established a 1-ha research plot in each of four forests (Guánica State Forest, Río Abajo State Forest, Guayama Research Area and Luquillo Experiment Forest) before September 2016, and had collected one full year data of litterfall production prior to the arrival of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 36 publications
4
38
0
1
Order By: Relevance
“…Overall, there was a very good ability to model the spatial variation of the hurricane effects with the simple models. Furthermore, the percentage of greenness loss in the region (31%) and the much larger amount in the LEF (51%), agrees with the small number of field studies that have been conducted so far [39,40]. The studies are not quite correspondent, since these other studies were focused on litterfall and tree damage (not equivalent to canopy greenness loss) and calculated greenness loss here was up to a month after the hurricane (because of satellite image quality limitations discussed in the methods).…”
Section: Discussionsupporting
confidence: 84%
“…Overall, there was a very good ability to model the spatial variation of the hurricane effects with the simple models. Furthermore, the percentage of greenness loss in the region (31%) and the much larger amount in the LEF (51%), agrees with the small number of field studies that have been conducted so far [39,40]. The studies are not quite correspondent, since these other studies were focused on litterfall and tree damage (not equivalent to canopy greenness loss) and calculated greenness loss here was up to a month after the hurricane (because of satellite image quality limitations discussed in the methods).…”
Section: Discussionsupporting
confidence: 84%
“…Using remote sensing techniques, one recent effort estimated that Maria caused immediate mortality or severe damage to 23-31 million trees (Feng et al, 2018). Similarly, forest plots sampled at four locations across Puerto Rico indicated that the pulse of litterfall associated Hurricanes Irma and Maria was equivalent to 95-171% of the mean annual total (Liu et al, 2018). However, litterfall from Hurricane Irma was actually greater than from Maria for the forest plot nearest to Irma's path, supporting the idea of an Irma-related LAI response in Figure 2a.…”
Section: Resultsmentioning
confidence: 99%
“…These disturbances alter the forest vegetation composition and productivity, through tree damage [3]. Hurricanes cause rapid deposition of significantly large amounts of leaf litter and woody debris from the canopy to the forest floor [4] , [5], [6], [7], which then results in short to long-term changes to the forest structure and forest ecological processes [4]. These processes are critical to forest recovery, and are associated with both the rapid increase in the carbon (C) and nitrogen (N) nutrients [8], [9], [10], [11] and the subsequent influences to the soil microbiota [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…There have been studies on the effects of hurricane-induced litter fall and enhanced soil nutrients on soil processes (especially decomposition) that have shown the patterns observed are a function of the characteristics of the specific hurricane, and that of the forest before the hurricane hit, making it difficult to predict specific effects from the hurricane-induced dropping of canopy material [8]. Moreover, much of the leading work has been conducted under hurricane simulation experiments in which canopy components are cut and dropped to the forest floor (for example: [6] [9] [14] [15] [16]), which leads to the important question of "what happens under real conditions and are they different?". Clearly, there is much work to be conducted, but doing work in the same forest location before and after a hurricane is truly a serendipitous opportunity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation